The protective effect of serum carotenoids on cardiovascular disease: a cross-sectional study from the general US adult population - Wang, Min; Tang, Renzhe; Zhou, Rui; Qian, Yongxiang; Di, Dongmei (Frontiers in Nutrition, 2023)
Background Cardiovascular disease (CVD) has become a key global health issue. Serum carotenoids are associated with CVD, while their effects on different diseases remain unclear. Herein, the relationship between the concentration of serum carotenoid and the CVD risk was investigated using nationwide adult samples obtained from the USA. Materials and methods Data of National Health and Nutrition Examination Survey (NHANES) in 2001–2006 were employed. The association of serum carotenoids (total, lycopene, β-carotene, α-carotene, lutein/zeaxanthin, and β-cryptoxanthin) with CVD was explored by using multivariate logistic, linear and weighted quantile sum (WQS) regression analyses. Eventually, data from 12,424 volunteers were analyzed for this study. Results Multivariate model data showed that lutein/zeaxanthin, α-carotene, lycopene, and β-cryptoxanthin were negatively associated with the prevalence of CVD (p < 0.05). In comparison with the first quartile, the fourth quartile was associated with α-carotene ([OR] = 0.61 [0.47–0.79]), β-cryptoxanthin (OR = 0.67 [0.50–0.89]), lutein (OR = 0.69 [0.54–0.86]), and lycopene (OR = 0.53 [0.41–0.67]). WQS analysis revealed that the combination of serum carotenoids had negative correlation with the prevalence of total CVD (OR = 0.88, 95% CI: 0.85–0.92, p < 0.001). Additionally, dose–response analysis demonstrated a negative linear association of hypertension with all the carotenoids involved (p > 0.05 for non-linearity). Conclusion The concentration of serum carotenoids had negative correlation with the prevalence of CVD, with a more significant negative effect against heart attack and stroke.